2007
DOI: 10.1007/s11160-007-9039-9
|View full text |Cite
|
Sign up to set email alerts
|

The diet of pygmy sperm whales, Kogia breviceps, stranded in New Zealand: implications for conservation

Abstract: The stomach contents of 27 pygmy sperm whales, Kogia breviceps, stranded on New Zealand beaches between 1991 and 2003 are reported. These individuals comprise 16 males, 10 females, and one for which no sex information is available. The diet was found to include fish and crustaceans, but is comprised primarily of cephalopods, with 0-526 lower beaks, representing an estimated maximum of c. 60 kg of cephalopod prey consumed by any one whale. Cephalopod prey is attributed to 23 species from 13 families, and is dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…Despite the substantial opportunity strandings have provided in terms of understanding the biology and ecology of cetacean populations in New Zealand waters, the diet of long-finned pilot whales, Globicephala melas, has been only recently reported (Beatson et al 2007a,b). Of approximately 30 odontocete species occurring in New Zealand waters, the diets of only three others have been described: sperm whale, Physeter macrocephalus (Gaskin & Cawthorn 1967;Clarke & MacLeod 1982;Clarke & Roper 1998;Gomez-Villota 2007); pygmy sperm whale, Kogia breviceps (Beatson 2007); and common dolphin, Delphinus sp. (Meynier et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the substantial opportunity strandings have provided in terms of understanding the biology and ecology of cetacean populations in New Zealand waters, the diet of long-finned pilot whales, Globicephala melas, has been only recently reported (Beatson et al 2007a,b). Of approximately 30 odontocete species occurring in New Zealand waters, the diets of only three others have been described: sperm whale, Physeter macrocephalus (Gaskin & Cawthorn 1967;Clarke & MacLeod 1982;Clarke & Roper 1998;Gomez-Villota 2007); pygmy sperm whale, Kogia breviceps (Beatson 2007); and common dolphin, Delphinus sp. (Meynier et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…listed as a dominant cephalopod prey in all other Pygmy Sperm Whale diet studies, except those from Taiwan (Wang et al 2002), and comprised 73% of the mass consumed by Pygmy Sperm Whales recovered from New Zealand (Beatson 2007). Histioteuthis atlantica has a circumglobal distribution in southern waters and is regularly found in ocean basins, and over shelves and plateaux (Voss et al 1998).…”
Section: Fig 2 -(A) % Numerical Abundance (%Num) and (B) % Reconstrumentioning
confidence: 99%
“…Plön (2004) found remains of the crustacean Neognathauphausia ingens Dohrn, 1870, as well as large quantities of Octopodidae, Enoploteuthidae, Histioteuthidae and Ommastrephidae (i.e., >20% mass/ individual), and smaller quantities of Chiroteuthidae, Octopoteuthidae, Ommastrephidae and Mastigoteuthidae (i.e., <20% mass/individual). Beatson (2007) investigated Pygmy Sperm Whale diet from 27 stranded individuals in New Zealand, where Pygmy Sperm Whales are one of the most frequently stranded cetacean species. Beatson (2007) found that the diet consisted primarily of mesopelagic cephalopods (23 species from 13 families, dominated by juvenile individuals of the families Histioteuthidae and Cranchiidae), with some fish and crustacean remains also present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods, such as stomach contents analysis, are common for fish species (Hyslop, 2006) but are generally not used for most birds and mammals unless the individuals are found dead (e.g. Beatson, 2007), while direct observation is usually prohibited by time or logistical constraints. Scat or pellet analysi s is a particularly useful inexpensive and non-invasive method of studying the feeding ecology of elusive carnivores (Ciucciet al, 1996;Maruccoet al, 2008).…”
Section: Introductionmentioning
confidence: 99%